836 An exploration of paediatric burn injuries, associated with cooking, in rural and Peri-Urban Malawi. (1st September 2016) - Beard, Maria; Watson, Michael; Clifford, Michael
Abstract : Background: Burn injury rates are especially high in Africa where exposure to unsafe cooking appliances and open fires pose significant dangers to children. While it has been suggested that the use of improved cookstoves (ICS) may mitigate a child's exposure to burn injuries more evidence is needed. The aim of this study is to explore factors which contribute to the incidence, cause and severity of paediatric burn injuries associated with cooking. Malawi was selected for this study as; children are at particularly high risk of burns because of the nature of the environments in which they live and the paucity of burn prevention programs. Methods: Data was collected across four sample sites. Each site had previous exposure to an ICS technology. Hospital data and community surveys were used to elicit the incidence of burns. Household interviews, focus groups and observations obtained narrative experiences from families whose children have, and have not, experienced burn injuries in the home. Interviews were undertaken with stove organisations to better understand existing quality control and safety standards in relation to ICS. Results: Results will include: hospital and community based data; parents attitudes towards to the causes of burn injuries; parents perception of hazards and safety within their compound; safety precautions practiced by parents in the home; barriers to preventing burns injuries; risk factors associated with the cooking process and the kitchen environment; existing measures used to determin the safety of ICS. Conclusions: The findings will show the key factors associated with paediatric burn injuries accross rural and peri-urban areas of Malawi. This infromation would support the advancement of cultrually and contextually appropriate interventions and policy relating to ICS programmes. The study recommendations may also be applied to a wider number of countries, whose population rely on similar cooking processes.